LINGUISTICS ANALYSIS: FIGURATIVE LANGUAGE USED IN ROBERT FROST’S POEM - Rida Fahas; Rizqi Husaini; Puput Jianggimahastu L.S; Dedy Richi R (SABBHATÃ YATRA : Jurnal Pariwisata dan Budaya, 2021)
This research aims to find out the most dominant figurative language that usedin poems of Robert Frost.This study includes to qualitative research with a objective approach to analyze the poems of Robert Frost‟s selected poems. The sources of data is obtained in this study by looking for books and internet that contains about literature and poetry. The writer uses note taking method in the collection of data that is by reading, writing and looking for poems of Robert Frost‟s selected poems related to the formulation of the problems. The technique of analysis of the data is by reading, identifying, understanding, finding, and making conclusion every poems which is analyzed from the poems of Robert Frost‟s selected poems related to the formulation of the problems in the study.The results of the study shows that the most dominant figurative language in the selected poems are two Metaphor, eleven personification, four symbol, three hyperbole, and one repetition. So, it can be coclude that this selected poems are dominate by “Personification”.